Studi Tentang Kebiasaan Petani Memupuk Padi Sawah di Desa Bener,Wonosari, Klaten - Ainur Rosidah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2019)
Rice cultivation is an activity that aims to get the highest yields with the best quality possible. Fertilization is one of the stages to get results that are in line with expectations, its function is so that the planted plants are healthy and fertile. Fertilization activities should be adjusted to the recommendations of the results of soil tests on agricultural land and the results of research on rice varieties to be used. The results of the study indicate that paddy fields are the main source of rice production. Changing a habit is not an easy job, especially with a high risk because it is associated with socio-cultural issues. Farmers' understanding of technological innovation requires mental readiness to make the decision to adopt it through the process of perception, because the adoption rate of an innovation depends on the adopter's perception of the characteristics of the technological innovation which include relative superiority, level of suitability, complexity, can be tried and can be observed. The purpose of this study was to find out the relationship between farmers 'characteristics and farmers' perceptions of the choice of fertilizer use for rice plants.